Patterns of Language Maintenance Among Algerian-Arabic Speakers in France - Flih Zahia (Darnioji daugiakalbystė)
For a very long time, France’s language policy has considered French as the only language of the republic, ignoring any other languages spoken across the country. In such a situation, immigrant minorities are most likely to experience significant challenges in preserving their heritage language. This paper addresses language maintenance and shift among the Algerian minority group in France, which represents the largest immigrant group with 12.7% of the total number of foreigners living in the country. It seeks to compare three generations by examining their language proficiency, language use, and language attitude in order to gauge the degree to which each generation is maintaining the heritage language. It also seeks to determine whether participants’ language proficiency and use are associated with their length of residence in the host country, age at immigration, and language attitudes. To reach these goals, a questionnaire was administered to the target population, together with interviews recorded with a smaller group in each generation. Based on the questionnaire data from 187 participants, the Kruskal-Wallis test revealed significant differences between the three generations in their self-reported proficiency and use of Arabic and French languages, which may be an indication of a gradual shift towards French. The interviews conducted with 11 participants suggested that the reasons behind such a shift are related to: prior exposure to the French language before migration, lack of exposure to the Arabic language, and experiences of discrimination and marginalization. The correlation between the extralinguistic variables and language proficiency has shown no relationship between participants’ length of residence and their level of proficiency in the Arabic language. However, age at immigration and attitude have positively and significantly correlated to participants’ Arabic language proficiency.